Polyethylene Glycol (PEG‐200): An Efficient, Green and Biocompatible Reaction Medium for the Metal‐Free Synthesis of Functionalized 1, 4‐Benzothiazines. Issue 2 (13th January 2023) - Islam, Aminul; Singha, Rabindranath; Ghosh, Pranab
Abstract: An efficient, simple and biocompatible one‐pot two‐component PEG‐200 catalysed approach for the synthesis of bioactive and medicinally important 1, 4‐benzothiazine derivatives from 2‐aminobenzothiols and 1, 3‐dicarbonyl compound has been demonstrated. Polyethylene glycol (PEG‐200) has proved to be a new class of green and biocompatible reaction media for the metal free organic synthesis. Abstract : In this research work, we synthesized functionalized 1, 4‐benzothiazine derivatives, a principal group of heterocyclic compounds, which reported to possess wide applications in medicinal chemistry. We used Polyethylene glycol (PEG‐200) as a new class of green and biocompatible reaction medium for the metal free synthesis of this biologically active heterocycle.